If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x+6=(x+3)
We move all terms to the left:
3x+6-((x+3))=0
We calculate terms in parentheses: -((x+3)), so:We get rid of parentheses
(x+3)
We get rid of parentheses
x+3
Back to the equation:
-(x+3)
3x-x-3+6=0
We add all the numbers together, and all the variables
2x+3=0
We move all terms containing x to the left, all other terms to the right
2x=-3
x=-3/2
x=-1+1/2
| -2-3c=-3c-9 | | 3x+6=2(x*3) | | x+80+72=180 | | 12x-1+70x=163 | | -18a-2=-19a-20 | | 0.35+.03b=0.45+.02b | | h+83/15=14 | | 2x+18=4x+14 | | 3.14x=6.3 | | -10-7g=-g+10-10g | | 4(x+6)2=52 | | 12d+4=5d+60 | | 152+5x+28=180 | | –2s=–3s+7 | | b–=4−3b | | 4y-1818=20 | | -5(5-3r)=-115 | | -13-9a=-10a | | 26-9h=4-3(h=3)-6h | | 5t-12=2.5t*20 | | 2p+3(p+3=21) | | 15-9j=9 | | (4x+24)2=52 | | 47(c-5)=-7 | | 5c+6=2c+45 | | 8z-8=7z | | -8-434=-4-6(9+8k) | | 3(x+2)=2x-6+x | | 19+8a=-5a-7+15a | | -1/4(-8x+16)=52 | | (4-2)=2x | | -6x=-33 |